UtopicSense: a tool to support the use of synesthesia as an assistive resource in 2D games - Silva, Adriel Augusto Germano; Coutinho, Flávio Roberto dos Santos (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2021: Anais do XX Simpósio Brasileiro de Jogos e Entretenimento Digital, 2021)
The concept of synesthesia in games comprises providing stimuli in more than one sense, such as displaying visual effects concurrently with sound effects on a screen. Algorithmic synesthesia is a concept that describes multimedia processes in which sounds, images, and in some cases, haptic sensations have as generators the same computational process or data source. Game developers can leverage such concept as an ancillary resource for people with hearing loss or deafness. Despite its advantages to the gaming experience, synesthesia is rarely contemplated in gaming design with the focus on accessibility. This situation usually happens because developers are unaware of its benefits or want to avoid additional costs and more implementation work on the project's schedule. This paper presents UtopicSense, a tool that automates implementing synesthesia in 2D games inside Unity. To create it, we identified positive and negative accessibility aspects perceived through the analysis of 2D games. We then developed the tool which allows users to configure aspects of the generated visual effects through a Unity custom editor panel. We evaluated the tool in terms of usability with potential users (Unity game developers). They provided feedback and evaluated the tool in terms of ease of use, flexibility, and usefulness. Participants expressed positive reactions towards UtopicSense and indicated that it fulfilled its goal of integrating algorithmic synesthesia into 2D games in an easier way.